2020
DOI: 10.1186/s13046-020-01599-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC00520 promotes the proliferation and metastasis of malignant melanoma by inducing the miR-125b-5p/EIF5A2 axis

Abstract: Background: Long intergenic non-protein coding RNA 520 (LINC00520), a novel identified lncRNA, has been shown to modulate the malignant phenotype of tumor cells in some malignant tumors. However, the exact role and molecular mechanism of LINC00520 in malignant melanoma has not been studied. Methods: The expression of LINC00520 in melanoma tissues were detected by using RNA-seq analysis and qRT-PCR. Melanoma cases from the public databases (The Cancer Genome Atlas (TCGA), GEO#GSE15605, GEO#GSE34460 and GEO#GSE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are a class of non-coding RNAs (ncRNAs) that contain >200 nucleotides ( 7 ). Recent studies have reported that the dysregulation of lncRNAs is involved in the development of multiple tumors, including melanoma ( 8 , 9 ). It has been reported that lncRNA small nucleolar RNA host gene 6 (SNHG6; ENSG00000245910) is involved in the progression of various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of non-coding RNAs (ncRNAs) that contain >200 nucleotides ( 7 ). Recent studies have reported that the dysregulation of lncRNAs is involved in the development of multiple tumors, including melanoma ( 8 , 9 ). It has been reported that lncRNA small nucleolar RNA host gene 6 (SNHG6; ENSG00000245910) is involved in the progression of various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of LINC00520 can promote the proliferation, invasion, and migration of melanoma. At present, there is no report on LINC00520 and autophagy in any type of tumor [38]. Therefore, further experimental veri cation is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…LINC00518 (p-value = 0.00803) has shown to act as a competing endogenous RNA to promote the metastasis of malignant melanoma via miR-204-5p/AP1S2 axis (Luan et al, 2019). Also, LINC00520 (p-value = 0.00931) promotes the proliferation and metastasis of malignant melanoma by inducing the miR-125b-5p/EIF5A2 axis (Luan et al, 2020). Another weighted gene co-expression network analysis show that the PI3K subunit PI3KCD exhibited excellent efficacy for diagnosing primary and metastatic tumor tissue (Wang et al, 2019).…”
Section: Differentially Expressed Lncrnas and Mrnas Associated To Surmentioning
confidence: 99%